Allergens displayed on virus-like particles are highly immunogenic but fail to activate human mast cells. - Engeroff, P; Caviezel, F; Storni, F; Thoms, F; Vogel, M; Bachmann, MF (Wiley, 2017)
Background The goal of allergen-specific immunotherapy is the induction of protective immune responses in the absence of anaphylactic reactions. We have previously shown that Fel d 1, the major cat allergen, displayed in a repetitive fashion on virus-like particles (VLPs) may fulfill these criteria. Specifically, Fel d 1 on VLPs induced strongly increased protective IgG responses compared to free allergen in mice while anaphylactic reactions were essentially abolished. Here we extend these findings to human mast cells and offer a mechanistic explanation for the reduced anaphylactic activity. Methods We differentiated human mast cells in vitro from blood-derived stem cell progenitors and sensitized the cells with a monoclonal Fel d 1-specific IgE. We compared the capability of Fel d 1 to induce mast cell activation in its free form versus displayed on VLPs and we performed allergen binding studies by surface plasmon resonance as well as flow cytometry. Results We show that free Fel d 1 induces degranulation of IgE-sensitized mast cells whereas Fel d 1 displayed on VLPs fails to induce mast cell activation. We demonstrate that this inability to activate mast cells is based on a biophysical as well as a biochemical mechanism. Firstly, Fel d 1 on VLPs showed a strongly impaired ability to bind to surface-bound IgE. Secondly, despite residual binding, repetitively displayed allergen on VLPs failed to cause mast cell activation. Conclusion These findings indicate that repetitively displaying allergens on VLPs increases their immunogenicity while reducing their potential to cause anaphylactic reactions by essentially eliminating IgE-mediated activation of mast cells.